2020
DOI: 10.1186/s13059-020-02179-w
|View full text |Cite
|
Sign up to set email alerts
|

Do malignant cells sleep at night?

Abstract: Biological rhythms regulate the biology of most, if not all living creatures, from whole organisms to their constitutive cells, their microbiota, and also parasites. Here, we present the hypothesis that internal and external ecological variations induced by biological cycles also influence or are exploited by cancer cells, especially by circulating tumor cells, the key players in the metastatic cascade. We then discuss the possible clinical implications of the effect of biological cycles on cancer progression,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 152 publications
0
21
0
Order By: Relevance
“…During the day, cancer cells manifest the Warburg phenotype associated with an elevated level of cytosolic glycolysis. On the other hand, at night tumors exhibit decreased aerobic glycolysis and metabolic reprogramming leading to OXPHOS, and thus cancer cells use mitochondrial oxidation of glucose to ATP generation [ 95 ]. Acquired data showed that metabolic reprogramming of cancer cells to healthy phenotype correlated with rising of circulating melatonin during the night.…”
Section: Structural and Functional Aspects Of Melatoninmentioning
confidence: 99%
“…During the day, cancer cells manifest the Warburg phenotype associated with an elevated level of cytosolic glycolysis. On the other hand, at night tumors exhibit decreased aerobic glycolysis and metabolic reprogramming leading to OXPHOS, and thus cancer cells use mitochondrial oxidation of glucose to ATP generation [ 95 ]. Acquired data showed that metabolic reprogramming of cancer cells to healthy phenotype correlated with rising of circulating melatonin during the night.…”
Section: Structural and Functional Aspects Of Melatoninmentioning
confidence: 99%
“…If cell intrinsic or external factors drive tumors to “shed” cells rhythmically, it is possible that CTCs might appear in the circulatory system at a predictable phase of the circadian rhythm with the number present undergoing an oscillation under the influence of circadian timing signals, as has been recently discussed [ 126 ]. A recent study using in vivo flow cytometry with mice reported daily rhythms in CTC abundance that also persisted in constant darkness, indicating the rhythm was endogenous and not merely driven by responses to the light cycle [ 50 ].…”
Section: Circadian Clocks Acting In Tumorigenesis and Metastasismentioning
confidence: 99%
“…It would also be beneficial to determine whether rhythmic properties of CTCs are driven by a circadian clock within the cells or by external timing signals originating in the surrounding circadian system. CTCs may, for example, benefit from a protective “temporal niche” when daily immune surveillance is minimal [ 126 ]. An early study by Hrushesky et al, 1999, indicated that the most effective phase for initiating tumor formation in mice after cancer cell injection is near the transition from sleep to waking, when darkness begins [ 129 ].…”
Section: Circadian Clocks Acting In Tumorigenesis and Metastasismentioning
confidence: 99%
“…Future prospective studies with large patient cohorts might focus on a single organ cancer type and OSA-related specific cancer biomarkers. Furthermore, as the circadian cycle alters cancer cell dissemination [ 63 ], the influence of OSA on circadian cycle disruption might be also addressed in future research. In conclusion, more evidence is needed to conclude that OSA plays a role in human cancer.…”
Section: Highlights From the Ers/european Sleep Research Society Sleep And Breathing 2021mentioning
confidence: 99%